Determination of the Effects of Carboxylic Acids on Calcium Sulfate Dihydrate Crystallization - SAYAN, PERVİZ; POLAT, SEVGİ (WILEY-V C H VERLAG GMBH, 2017)
Calcium sulfate dihydrate crystallization was carried out using a mixed-suspension mixed-product removal (MSMPR)-type crystallizer in pure media and in the presence of three different types of carboxylic acid: propionic acid, oxalic acid, and propane-1,2,3-tricarboxylic acid. The crystal size distributions and filtration rates of the calcium sulfate dihydrate crystals were measured, and the crystals obtained were analyzed using a thermogravimetric analyzer coupled with a Fourier transform infrared spectrometer and mass spectrometer (TGA-FTIR-MS). The average particle size, length-to-width ratio of the crystals, and the filtration rate of calcium sulfate dihydrate crystals were decreased in the presence of all three carboxylic acids when compared to the pure media. TGA-FTIR-MS indicated that all carboxylic acids adsorbed onto the calcium sulfate dihydrate crystals.
Keywords: Calcium sulfate dihydrate; Carboxylic acids; Crystallization; SIMULATED CONDITIONS; KINETIC-ANALYSIS; DECOMPOSITION